“TINJAUAN FIQH JINAYAH TERHADAP SANKSI BAGI PELAKU PEMBUANG SAMPAH SEMBARANGAN MENURUT PERDA KOTA MEDAN NOMOR 6 TAHUN 2015 TENTANG PENGELOLAAN PERSAMPAHAN ” - Matondang, Maulidya Mora (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2022)
Garbage is leftover material from human and natural activities. The problem of waste has not been resolved until now. The lack of awareness of everyone to protect the environment can be seen from the amount of waste that is not in its place. This research is a library research or library research. Based on the results of the study, the authors conclude that littering as stipulated in the Medan City Regional Regulation Number 6 of 2015 concerning Garbage Management, littering is prohibited and there are criminal provisions as Article 32 and Article 35 of Medan City Regional Regulation Number 6 of 2015 2015 concerning Waste Management, namely for people who throw garbage carelessly, they are threatened with imprisonment for a maximum of 3 (three) months or a fine of up to Rp. 10,000,000.00 (ten million rupiahs) whereas, for legal entities that commit it, they are subject to a maximum imprisonment 6 (six) months or a maximum fine of Rp. 50,000,000.00 (fifty million rupiah). Judging from the sanctions that have been stipulated in the regional regulation, the implementation that has taken place in the field has not gone according to what has been stipulated. This results in many people throwing garbage carelessly and causing even greater adverse impacts. In Fiqh Jinayah or Islamic Criminal Law, behavior that can harm living things is said to be jinayah behavior. Disposing of garbage indiscriminately can be categorized as ta'zir, where the sanctions against the offender are not specified in the texts, even though the Koran prohibits damaging the environment, the effect can threaten human rights, namely destroying the objectives of Islamic law itself, which is commonly referred to as maqasid Sharia. maintaining religion, soul, mind, lineage, and property.